2015
DOI: 10.1093/infdis/jiv054
|View full text |Cite
|
Sign up to set email alerts
|

Effector Phenotype ofPlasmodium falciparum–Specific CD4+T Cells Is Influenced by Both Age and Transmission Intensity in Naturally Exposed Populations

Abstract: These findings highlight major differences in the CD4(+) T-cell response of immune adults and nonimmune children that may be relevant for immune protection from malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 46 publications
3
45
0
Order By: Relevance
“…Additional studies using multiparameter flow cytometric analysis of peripheral blood mononuclear cells (PBMCs) from asymptomatic children with higher exposures revealed a skewness towards an immune‐regulatory effector phenotype of CD4 + T cells 106. A higher proportion of CD4 + T cells that produce IL‐10 and coproduce IFN‐ γ and IL‐10 were observed in children from the high‐transmission area, whereas CD4 + T cells of children from the low‐transmission area predominantly produced IFN‐ γ , TNF‐ α and/or IL‐2, suggesting increased inflammatory responses in children at low exposure levels 56, 106.…”
Section: Reduced Inflammation: a Potential Parasite Tolerance Mechanimentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies using multiparameter flow cytometric analysis of peripheral blood mononuclear cells (PBMCs) from asymptomatic children with higher exposures revealed a skewness towards an immune‐regulatory effector phenotype of CD4 + T cells 106. A higher proportion of CD4 + T cells that produce IL‐10 and coproduce IFN‐ γ and IL‐10 were observed in children from the high‐transmission area, whereas CD4 + T cells of children from the low‐transmission area predominantly produced IFN‐ γ , TNF‐ α and/or IL‐2, suggesting increased inflammatory responses in children at low exposure levels 56, 106.…”
Section: Reduced Inflammation: a Potential Parasite Tolerance Mechanimentioning
confidence: 99%
“…A higher proportion of CD4 + T cells that produce IL‐10 and coproduce IFN‐ γ and IL‐10 were observed in children from the high‐transmission area, whereas CD4 + T cells of children from the low‐transmission area predominantly produced IFN‐ γ , TNF‐ α and/or IL‐2, suggesting increased inflammatory responses in children at low exposure levels 56, 106. Similarly, CD4 + T cells from children with ≥ 2 prior episodes of malaria also coproduced IFN‐ γ and IL‐10 after stimulation with infected RBCs (iRBCs), whereas CD4 + T cells from children with fewer than two prior malaria episodes produced TNF‐ α only, without the co‐production of IL‐10,107 also demonstrating the predisposition towards an inflammatory state in children with fewer exposure histories.…”
Section: Reduced Inflammation: a Potential Parasite Tolerance Mechanimentioning
confidence: 99%
“…By using PBMC samples collected from Timika, Indonesia, where 125 million people live in malaria-endemic regions 323 , we found that IL-10 production was dependent on type I IFN's, post Contrastingly, in a high transmission setting, children have higher frequencies of parasite-specific CD4 + T cells producing IL-10, whereas the CD4 + T cells in adults produce IFNγ and TNF 48 .…”
Section: Discussionmentioning
confidence: 85%
“…While γδ T cells have been shown to produce IFNγ in response to parasite antigen, they were greatly outnumbered by αβ T cells 55 and this was observed in our studies (Fig 4 b). Earlier studies have shown CD4 + T cells to be a predominant source of IFNγ in response to parasite antigen 48,55,56 . While the contribution to IFNγ production by CD4 + and CD8 + T cells was relatively equal, CD4 + T cells were the main producers of IFNγ in response to parasite antigen 14 days post challenge (Fig 4c).…”
Section: Cd4 + T Cells Are the Predominant Source Of Ifnγ During Bloomentioning
confidence: 99%
See 1 more Smart Citation